Full title of manuscript: Five new species of the genus Hylaeus (Hymenoptera: Colletidae) from China - Chen, Huan; Xu, Huanli (Zootaxa, 2013)
Five new species, Hylaeus (Hylaeus) wuae sp. nov., H. (Hylaeus) napacus sp. nov., H. (Hylaeus) neatifrons sp. nov., H. (Hylaeus) bimaculatus sp. nov. and Hylaeus (Prosopis) ikudomei sp. nov. are described and illustrated from Yunnan, Chi-na. The diagnosis of each species is provided. In addition, Hylaeus cardioscapus Сockerell, 1924 is recorded from China for the first time.